The potential of the socialprotection.org platform to support policymaking and innovation on social protection: Overview of the impact of the platform from September 2015 to December 2018 - Aline Peres; Ashleigh Slingsby; Mariana Balboni (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
There has been major progress in the reduction of extreme poverty globally in the past 25 years. According to the most recent poverty data produced by the World Bank (2018), the extreme poverty rate fell from 36 per cent in 1990 to 10 per cent in 2015. However, extreme poverty rates remain persistently high in low-income countries and in those countries most affected by conflict and political unrest. In addition, the speed of the decline has slowed, which raises concerns about the feasibility of reaching the poverty-related targets of the Sustainable Development Goals (SDGs) by 2030.
Keywords: 330; potential; socialprotection.org; platform; support; policymaking; innovation; social protection